2006
DOI: 10.1007/s10722-006-9009-4
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of aroma patterns in wild and cultivated Fragaria accessions

Abstract: Plant breeders are interested in strawberry species as donors of volatile compounds in breeding programmes because of the diversity and intensity of wild strawberry aroma. Therefore, the topic of this paper is the prospective analysis of four accessions of four wild strawberry accessions in comparison to a standard cultivar of Fragaria · ananassa Duch. by using human sensory, gas chromatography mass spectrometry (GCMS) and gas chromatographyolfactometry (GCO). The wild species have higher aroma intensities com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
116
2
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(134 citation statements)
references
References 20 publications
(16 reference statements)
11
116
2
5
Order By: Relevance
“…The total level of esters at harvest was 3.84 µg/kg. After 48 h of storage at 1 ± 1°C, all treatments showed a decrease in the total amount of esters, while at 96 h with a change in temperature to 18 ± 1°C, and in agreement with the literature (Ulrich, Komes, Olbricht & Hoberg, 2007), the levels increased probably due to water loss (data not shown) and increase in CO 2 concentration inside the packages wrapped with the biodegradable film both in passive and active MAP (treatments A and B) (Ke, Zhou & Kader, 1994). Some compounds, such as 2-hexenyl acetate, phenethyl acetate and ethyl benzoate, were not found in the fruits at harvest or after 48 h of storage at 1 ± 1°C; they were instead synthesized at 18 ± 1°C.…”
Section: Fruit Volatile Componentssupporting
confidence: 92%
“…The total level of esters at harvest was 3.84 µg/kg. After 48 h of storage at 1 ± 1°C, all treatments showed a decrease in the total amount of esters, while at 96 h with a change in temperature to 18 ± 1°C, and in agreement with the literature (Ulrich, Komes, Olbricht & Hoberg, 2007), the levels increased probably due to water loss (data not shown) and increase in CO 2 concentration inside the packages wrapped with the biodegradable film both in passive and active MAP (treatments A and B) (Ke, Zhou & Kader, 1994). Some compounds, such as 2-hexenyl acetate, phenethyl acetate and ethyl benzoate, were not found in the fruits at harvest or after 48 h of storage at 1 ± 1°C; they were instead synthesized at 18 ± 1°C.…”
Section: Fruit Volatile Componentssupporting
confidence: 92%
“…Eugenol is the main phenylpropanoid volatile compound that contributes to strawberry aroma (Pyysalo et al, 1979;Ulrich et al, 1995Ulrich et al, , 2007Zorrilla-Fontanesi et al, 2012). In ripe strawberry fruits, eugenol is biosynthesized by the action of FaEGS2, whose coding gene has a ripening-related expression pattern and presents its maximum expression at the red-ripe stage (Aragüez et al, 2013).…”
Section: Faeobii Expression Is Ripening Related and Correlates With Ementioning
confidence: 99%
“…In these studies, more than 360 volatiles have been identified (Latrasse, 1991;Nijssen, 1996;Zabetakis and Holden, 1997), but only 15 to 20 of them in wild varieties of strawberry are believed to be essential for sensory quality, together with nonvolatile sugars and organic acids (Schieberle and Hofmann, 1997). In contrast, in cultivated varieties of strawberry, only about six odor-active compounds have been identified as contributors to fruit flavor (Raab et al, 2006;Ulrich et al, 2007). Strawberry aroma is the result of the combined perception of fruity (ethyl butanoate, ethyl hexanoate, and methyl 2-methylbutanoat), green (Z-3-hexenal), sweaty (butanoic acid and 2-methylbutanoic acid), peach-like (g-decalactone), and caramel-like [4-hydroxy-2,5-dimethyl-3(2H)-furanone and 2,5-dimethyl-4-methoxy-3(2H)-furanone] flavor notes (Pyysalo et al, 1979;Larsen and Poll, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method exploits variation between cultivars of the same species or between closely related species (9)(10)(11). In tomato, populations of introgression lines (ILs) that contain only a fragment of the genome of a wild species have been useful in the discovery of numerous volatile-associated QTL (10,12) as well as of QTL affecting yield, carotenoid production, and accumulation of primary metabolites (13,14).…”
mentioning
confidence: 99%